Cross-regulatory interaction between the HPI axis and appetite regulation in Atlantic salmon (Salmo salar) parr under chronic and acute stress - Lai, Floriana; Rønnestad, Ivar; Stien, Lars Helge; Madaro, Angelico (Frontiers in Endocrinology, 2025)
Reduced feed intake is a common stress response in Atlantic salmon (Salmo salar), yet the interaction between the stress-related hypothalamic–pituitary–interrenal (HPI) axis and the appetite-regulating hypothalamic melanocortin system remains poorly understood. This study explored the potential cross-regulatory interaction between these two systems by assessing feed intake, gastrointestinal content, and hypothalamic mRNA expression of crf1 paralogs, a key factor in stress handling, and appetite-related genes npy, agrp1, pomc, and cart in Atlantic salmon parr exposed to 21 days of unpredictable chronic stress, followed by a novel acute stressor. Our results indicated that regulation of the HPI axis and appetite-regulatory mechanisms appeared to depend on the type and duration of stress. Chronic stress reduced feed intake and gut content and increased feed conversion ratio, without changes in hypothalamic crf1 paralog expression but with reduced orexigenic npya1 transcript levels. Simultaneously, levels of the anorexigenic cart2b transcript variant were also reduced, possibly reflecting a compensatory response to prolonged appetite suppression. In contrast, exposure to the novel acute stressor induced a transient increase in crf1 paralogs and upregulated orexigenic neuropeptides npya1 and npya2, suggesting compensatory regulation to counteract stress-induced anorexia. In contrast, cart2b expression normalized to control levels, possibly reflecting an acute stress-induced compensatory response restoring appetite regulation. These results highlight a dynamic, stress-duration-dependent interaction between stress and appetite-regulatory systems in Atlantic salmon.